Wound Ballistics Basics and Applications - Kneubuehl, Beat P.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2022)
The definitive interdisciplinary reference work for wound ballistics Basics The book begins by providing the necessary basic knowledge about physics, ballistics and ammunition and weapons. Then it describes the behaviour of projectiles in humans and animals (the physics of gunshot injuries) and introduces the experimental simulation of gunshot wounds, including the materials suitable for this purpose. Applications These basic principles can be applied in forensic medicine and criminalistics. The gunshot wound provides some forensic traces and the experimental reconstruction helps to understand the dynamic crime process. The wounding potential of non-lethal weapons can be determined. In emergency and war surgery, injuries caused by small arms bullets and fragments as well as by gas jets (of gas weapons) can be assessed. International conventions could be freed from undefined terms (such as (3z(Bunnecessary suffering(3y(B) with the help of physical quantities. Reference work Detailed tables as e. g. ballistic data of numerous cartridge types, also older ones, material properties, as well as many otherwise difficult to access data and a trilingual glossary of ballistic and technical terms in the languages German, English and French. NEW Wound Ballistics of European Police ammunition References to recent research results Partly coloured illustrations Due to the increase in terrorist and criminal activities worldwide, it is not only members of the armed forces who are affected. Surgeons, forensic doctors, police officers and criminalists also need to know and be able to assess the specifics of gunshot wounds.s
Introduction -- Basics -- General wound ballistics -- Wound ballistics of bullets and fragments -- Wound ballistics and forensic medicine -- Wound ballistics and surgery -- Wound ballistics and international agreements -- Appendies. Tables -- Glossary -- Bibliography -- Index.
Keywords: Medical jurisprudence; Surgery; Emergency medicine; Pathology; Criminology; Forensic Medicine; General Surgery; Emergency Medicine; Pathology; Criminology; Wounds, Gunshot; Forensic Ballistics